2014
DOI: 10.1007/s40097-014-0112-3
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles using extract of olive leaf: synthesis and in vitro cytotoxic effect on MCF-7 cells

Abstract: A green synthetic approach using olive leaf extract was optimized for preparing silver nanoparticles (AgNPs). Parameters affecting the formation of nanoparticles such as temperature, exposure time to extract, pH, concentration of silver nitrate, and extract (ratio of plant sample to extraction solvent) were investigated and optimized. Optimum conditions for the synthesis of silver nanoparticles are as follows: Ag ? concentration 1 mM, extract concentration, 8 % w/v; pH = 7, time, 4 h and temperature, 45°C. Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 23 publications
(26 reference statements)
4
28
1
Order By: Relevance
“…We also observed that changing pH varied the colour of reaction which is ascertained to the difference in dissociation constants (pKa) of functional groups present in AHRE. Our findings are consistent with the previous studies where AgNPs were synthesized using Olea europaea leaf extract [20].…”
Section: Effect Of Ph On Agnps Synthesissupporting
confidence: 93%
See 1 more Smart Citation
“…We also observed that changing pH varied the colour of reaction which is ascertained to the difference in dissociation constants (pKa) of functional groups present in AHRE. Our findings are consistent with the previous studies where AgNPs were synthesized using Olea europaea leaf extract [20].…”
Section: Effect Of Ph On Agnps Synthesissupporting
confidence: 93%
“…Our results are supported by the study of Verma and Mehata [17] where they reported shift of absorption spectra towards lower wavelength with increasing temperature. Similarly, Rashidipour and Heydari [20] studied the effect of different temperatures (20,30,45, 60 C) on AgNPs synthesis using Olea europaea leaf extract and reported that rapid reduction of Ag þ occurred at higher temperature (45 C).…”
Section: Effect Of Temperature On Agnps Synthesismentioning
confidence: 99%
“…Rosano-Ortega et al (2006) proposed an application of the water hyacinth biomass for the Mn reduction from a MnSO4 solution and observed the dependence of the nanoparticle´s size as follows pH conditions, in which the smallest clusters (1-4 nm) were generated using a pH=5. Thus a change in pH gave it a modification of the chemical state (ionization) of the phytochemicals in plants, which affects their capacity to reduce metal ions (Makarov et al, 2014;Rashidipour et al, 2014). Water hyacinth was considered as a research subject due to the following characteristics: i).…”
Section: Introductionmentioning
confidence: 99%
“…ii). Accepts polyphenolic compounds in all sections of plants; But leaves contain a greater amount of these due to the plant's defense mechanism (Rashidipour et al, 2014). Because of these characteristics, polyphenolic compounds contribute to the reduction of silver and gold ions.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of plants, used in green synthesis, include active molecules acting as reducing and capping agents such as flavonoids, tannins, amines, aldehyde/ketone groups and polyols and proteins for Ag + [16–18]. Syntheses of silver nanoparticles using black pepper leaf extract [19], olive leafs [20], cinnamon barks [21], grape seed extract [22], or papaya fruit extract [23] have been reported.…”
Section: Introductionmentioning
confidence: 99%